Medial unicompartmental knee arthroplasty wear prediction using a total knee joint finite element model - Zhu, Xiaoyu; Mao, Zuming; Li, Rongkang; Ma, Shuqin; Lv, Ruolan; Zhao, Feng (Frontiers in Bioengineering and Biotechnology, 2026)
BackgroundUnicompartmental knee arthroplasty (UKA) often fails due to osteoarthritis (OA) progression, insert wear, and other associated risks. Current wear studies on UKA focus on isolated prostheses, neglecting bones, cartilage and other knee joint structures. The aims of this study were to predict the wear of tibial inserts under simulated physiologically mechanical environment, investigate the influence of the presence of bone and cartilage tissue on wear simulation results, and explore the effect of wear on the mechanical environment of the lateral compartment.MethodsTwo finite element models were developed: a UKA model consisting solely of prostheses, and a UKA total knee joint model (UKAK) incorporating prostheses, bones, cartilage, meniscus, and ligaments. Contact stress and wear prediction of medial inserts were analyzed under ISO standard loading. Furthermore, in the UKAK model, both wear prediction and the impact of wear on the lateral tibial cartilage were simultaneously examined.ResultsThe mass wear rates of UKA and UKAK model were 9.62 mg/million cycles and 7.41 mg/million cycles, respectively. The higher wear rate of the UKA model implied more evaluation testing requirements for the prosthesis. In contrast, the UKAK model, which better simulates physiological conditions, demonstrated that the maximum von Mises stress on the lateral tibial cartilage increased during the stance phase as gait cycles accumulated. After 5 million cycles, this stress increased by 27.53% at 43% of the stance phase compared to initial levels.ConclusionWear of the medial insert may increase lateral compartment cartilage stress, which may represent a potential mechanical risk factor associated with OA progression. This study provided support for the design optimization and clinical application of prostheses, and provided biomechanical data for the impact of wear on the mechanical environment of the lateral compartment.